Robust multi-dimensional trust model for improving the survivability of ad hoc networks - CHEN Shen-long1; ZHANG Yu-qing1 (Tongxin xuebao)
Attackers could perform the blended attack against ad hoc networks through utilizing several attack methods together.Under this circumstance,a robust multi-dimensional trust model（RMTM） to improve the survivability of ad hoc networks was proposed.RMTM was based on D-S theory.Nodes’ attack evidences were classified into several dimen-sions and the trust of each dimension was computed according to basic probability assignment function.Then RMTM implemented the comprehensive evaluation through the multi-dimensional trust fusion.In order to resist the attacks against trust models themselves,the corresponding tolerant algorithms were designed to enhance the RMTM’s robustness.The simulations show that RMTM can effectively defense against both ad hoc network blended attack and trust model attacks with limited overload and consequently it significantly improves the survivability of ad hoc networks.